Satisfaction of Domestic Leisure Travel based on Age Range: Case of Japan - Kenichi Shimamoto (International Review of Management and Marketing, 2019)
Tourism has a large effect on lifestyle, society and the economy. With policy goals aiming to develop Japan into a tourism nation, it has become important for Japan to understand tourism trends and satisfaction. This paper focuses on tourists' satisfaction based on age range for Japan domestic leisure travel with overnight stays by Japan residents. It examines the characteristics concerning the satisfaction of the travellers by each age range. The results find that the younger age ranges trend to be relatively ‘satisfied' with their travels and the older age ranges were relatively dissatisfied, with the 50s and 60s age ranges showing a strong tendency of being ‘very dissatisfied'. The age range closest to the average was the 40s.